Tell this question ... for 80 points and if wrong answer will be there then his account will be removed.
![](https://hi-static.z-dn.net/files/d71/83b7c7358deda13b07ee9395584949d3.jpg)
Answers
Hi buddy
Here is your answer
Put the value of n as 1in equation1
Put the value of n as 1in equation1⇒S₁ = 3(1)² + 5(1)
Put the value of n as 1in equation1⇒S₁ = 3(1)² + 5(1)⇒S₁= 3 + 5
Put the value of n as 1in equation1⇒S₁ = 3(1)² + 5(1)⇒S₁= 3 + 5⇒T₁ = 8
Now, put value of n as 2
Now, put value of n as 2⇒S₂ = 3(2)² + 5(2)
Now, put value of n as 2⇒S₂ = 3(2)² + 5(2)⇒S₂ = 12 + 10
Now, put value of n as 2⇒S₂ = 3(2)² + 5(2)⇒S₂ = 12 + 10⇒S₂ = 22
So, T₁ + T₂ = 22
So, T₁ + T₂ = 22⇒8 + T₂ = 22
So, T₁ + T₂ = 22⇒8 + T₂ = 22⇒T₂ = 22 - 8
So, T₁ + T₂ = 22⇒8 + T₂ = 22⇒T₂ = 22 - 8⇒T₂ = 14First term(a) = 8
First term(a) = 8Common difference (d) = 14 - 8 = 6
First term(a) = 8Common difference (d) = 14 - 8 = 6ak(an) = 164
First term(a) = 8Common difference (d) = 14 - 8 = 6ak(an) = 164Using Formula⇒a + (k - 1)d = 164
⇒a + (k - 1)d = 164⇒8 + (k - 1)6 = 164
⇒a + (k - 1)d = 164⇒8 + (k - 1)6 = 164⇒6k - 6 = 164 - 8
⇒a + (k - 1)d = 164⇒8 + (k - 1)6 = 164⇒6k - 6 = 164 - 8⇒6k = 164 + 6 - 8
⇒a + (k - 1)d = 164⇒8 + (k - 1)6 = 164⇒6k - 6 = 164 - 8⇒6k = 164 + 6 - 8⇒6k = 162
⇒a + (k - 1)d = 164⇒8 + (k - 1)6 = 164⇒6k - 6 = 164 - 8⇒6k = 164 + 6 - 8⇒6k = 162⇒k = 162/6
⇒a + (k - 1)d = 164⇒8 + (k - 1)6 = 164⇒6k - 6 = 164 - 8⇒6k = 164 + 6 - 8⇒6k = 162⇒k = 162/6⇒k = 27
Hope it help you
Please mark me please
#sibi ❤️
Answer:
hope it will help you. thanks
![](https://hi-static.z-dn.net/files/d8d/8428a44eb12a7d7b8aaca77b67208e14.jpg)